Critical modeling issues of SiGe semiconductor devices - Vassil Palankovski; Siegfried Selberherr (Journal of Telecommunications and Information Technology, 2004)
We present the state-of-the-art in simulation of silicon-germanium (SiGe) semiconductor devices. The work includes a detailed comparison of device simulators and current transport models. Among the critical modeling issues addressed in the paper, special attention is focused on the description of the anisotropic majority/minority electron mobility in strained SiGe grown on Si. We use a direct approach to obtain scattering parameters S-parameters and other derived figures of merit of SiGe heterojunction bipolar transistors (HBTs) by means of small-signal AC-analysis. Results from two-dimensional hydrodynamic simulations of SiGe HBTs are presented in good agreement with measured data. The examples are chosen to demonstrate technologically important issues which can be addressed and solved by device simulation.